Pengaruh Rebusan Minyak Atsiri Daun Sirih Merah (Piper Crocatum) sebagai Bahan Pembersih Gigi Tiruan Resin Akrilik terhadap Kekasaran Permukaan dan Perubahan Warna - Rismawati Tri Kalasworojati; Ady Soesetijo; R. Rahardyan Parnaadji (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2020)
Acrylic resins are frequently used as the basic materials of dentures in daily dental practices. Submersion of dentures in disinfectant is usually done by denture users to prevent plaque accumulation. Red betel leaf decoction and essential oils of red betel leaf 10% and 25% can be used as an alternative natural disinfectant contain polyphenols, because it can inhibit the growth of Candida albicans which is commonly found in prosthesis denture users. On the other hand, the polyphenols of red betle leaves was predicted can affect the roughness and discoloration of acrylic resin. The purpose of this study was to determine the differences in surface roughness and discoloration of heat cured acrylic resin submersed in decoction of red betel leaf and essential oil of red betel leaf 10% and 25%. This study was a laboratory experimental with pre and post test group design research.measuring surface roughness value with surface roughness TR 220 and discoloration value with color reader TCR 200. Conclusion: there is a difference in surface roughness and discoloration of acrylic resin that is submersed in decoction of red betel leaves and essential oils of red betel leaf 10% and 25%.